The Kinocilia of Cochlear Hair Cells: Structures, Functions, and Diseases - Wang, Difei; Zhou, Jun (Frontiers in Cell and Developmental Biology, 2021)
Primary cilia are evolutionarily conserved and highly specialized organelles that protrude from cell membranes. Mutations in genes encoding ciliary proteins can cause structural and functional ciliary defects and consequently multiple diseases, collectively termed ciliopathies. The mammalian auditory system is responsible for perceiving external sound stimuli that are ultimately processed in the brain through a series of physical and biochemical reactions. Here we review the structure and function of the specialized primary cilia of hair cells, termed kinocilia, found in the mammalian auditory system. We also discuss areas that might prove amenable for therapeutic management of auditory ciliopathies.